Correlation between Glycated Hemoglobin and Calcium Levels in Pediatric with Type 1 Diabetes Mellitus - Nasution, Indah; Arto, Karina Sugih; Lubis, Bugis Mardina (Journal of Society Medicine, 2023)
Introduction: Type 1 diabetes mellitus is a systemic disorder resulting from impaired glucose metabolism characterized by chronic hyperglycemia. Caused by damage to pancreatic β cells either by autoimmune or idiopathic processes resulting in reduced or even halted insulin production. Diabetes mellitus is associated with a decrease in calcium with impaired intestinal calcium absorption and hypercalciuria which causes a decrease in calcium absorption into the body. Method: This study used a prospective study method to assess the correlation between HbA1C levels and calcium levels in children with type 1 diabetes mellitus. This research was conducted  in the Endocrinology Outpatient Unit of Haji Adam Malik Hospital Medan, May 2022 to December 2022. The samples were children aged 1 month to 18 years. Results: Correlation is measured using Pearson correlation analysis for normally distributed data while Spearman correlation is used for data that was not normally distributed. There is a significant correlation between the HbA1c and calcium levels with a p value of 0.026 and a correlation value of (r= -0.445). The correlation value is negative, meaning that every increase in HbA1c levels will be followed by a decrease in serum calcium levels in children with type I diabetes, with moderate strength (r= 0.4 – 0.6). This effect is not influenced by diseases duration and onset of diabetes. Conclusion: There is a decrease in calcium in type 1 diabetes